2008
DOI: 10.1007/s00423-008-0396-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sequential organ failure assessment score for patients with strangulation ileus

Abstract: Background We examined the effectiveness of sequential organ failure assessment (SOFA) score to describe patients with strangulation ileus. Methods The subjects consisted of 66 patients given a diagnosis of ileus who underwent a surgery during the period from January 2001 to December 2006. On the basis of surgical findings, they were classified into two groups; the strangulation group, consisting of 25 patients, and the control group, consisting of 41 patients with simple ileus. The background factors, SOFA sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…demonstrated a strong correlation between strangulated ileus, mortality and the SOFA score. [ 9 ] Consistent with these findings, our study showed a significantly higher SOFA score in the ICU-requiring group. This may be attributed to partial organ dysfunction caused by systemic inflammatory mediators released from the small intestine after partial ischaemia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…demonstrated a strong correlation between strangulated ileus, mortality and the SOFA score. [ 9 ] Consistent with these findings, our study showed a significantly higher SOFA score in the ICU-requiring group. This may be attributed to partial organ dysfunction caused by systemic inflammatory mediators released from the small intestine after partial ischaemia.…”
Section: Discussionsupporting
confidence: 89%
“…These factors can lead to bacterial translocation, electrolyte imbalances and even sepsis. [ 9 ] Identifying high-risk patients and predicting the need for ICU admission can facilitate closer monitoring and potentially reduce mortality and morbidity. In our study, we aimed to predict post-admission ICU requirement in ASBO patients using the SOFA score, CCI and CRP/albumin ratio.…”
Section: Discussionmentioning
confidence: 99%